badge image

Enroll For Free Now & Improve Your Performance.

×
User Icon
User Icon
User Icon
User Icon
User Icon

Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
Grade: 12th pass

                        

Solve the equation if a²+b²+c²=2(a-b-c)-3 then find out the value of 2a-3b+4c=?

4 years ago

Answers : (2)

jagdish singh singh
173 Points
							
\hspace{-0.7 cm}$ we can write $a^2+b^2+c^2=2(a-b-c)-3$\\\\ as $a^2-2a+1+b^2+2b+1+c^2+2c+1=0$\\\\ So $(a-1)^2+(b+1)^2+(c-1)^2=0$\\\\ Using sum of square of all three real quantity is zero, if all are zero\\\\ So $a-1 = 0$ and $b+1 = 0$ and $c+1=0$\\\\ So $a=1\;\;,b=-1\;\;,c=-1$. So $2a-3b+4c =2+3-4=1 $
4 years ago
ankit singh
askIITians Faculty
596 Points
							
a² + b² + c² = 2 (a - b - c ) - 3
=> a² + b² + c² = 2a - 2b - 2c -3
=> a² + b² + c² - 2a + 2b + 2c + 3 = 0
//rearrange the above as below
=> a² - 2a + 1 + b² + 2b + 1  + c² + 2c + 1 = 0
=> (a-1)² + (b+1)² + (c+1)² = 0
Using sum of all three real quantity is zero, if all are zero
=>  a - 1  = 0 => a = 1
     b + 1  = 0  => b = -1
     c + 1 = 0 => c = - 1
Thus value of 2a - 3b + 4c = 2 * 1 - 3(-1) + 4(-1) = 1
3 months ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies


Course Features

  • 731 Video Lectures
  • Revision Notes
  • Previous Year Papers
  • Mind Map
  • Study Planner
  • NCERT Solutions
  • Discussion Forum
  • Test paper with Video Solution


Course Features

  • 101 Video Lectures
  • Revision Notes
  • Test paper with Video Solution
  • Mind Map
  • Study Planner
  • NCERT Solutions
  • Discussion Forum
  • Previous Year Exam Questions


Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details